Thoughts on American Manufacturing Decline and Revitalization - Timothy J. Bartik (W.E. Upjohn Institute for Employment Research, 2003)
The recent decline in American manufacturing probably reflects long-run problems. A sensible approach to revitalizing American manufacturing would focus on overcoming inefficiencies in the development of manufacturing, such as problems in small- and medium-sized manufacturers getting information about deploying new technologies. This approach to revitalizing manufacturing can best be implemented through federal efforts to encourage and support state and local economic development policies that help enhance manufacturing productivity. A decentralized approach to the revitalization of manufacturing encourages a variety of creative policies, is adaptable to local conditions, and is consistent with American political traditions.
Keywords: R58; R1; L52; L60; H77; 330; manufacturing; revitalization; technology; Bartik